2009
DOI: 10.1007/s00404-009-1073-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing GnRH agonist long protocol and gnrh antagonist protocol in outcome the first cycle of ART

Abstract: GnRH-antagonist is an effective, safe, and well-tolerated alternative to agonist in the first cycle of ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…This outcome measure was evaluated in 15 studies [8][12], [15][19], [21], [24][26], [28] (2,807 cases; the unified international standard unit pg/ml was adopted, with a conversion factor of 3.67), and heterogeneity was observed among various trials ( P <0.00001, I 2  = 96%). Therefore, a random-effect model was used for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This outcome measure was evaluated in 15 studies [8][12], [15][19], [21], [24][26], [28] (2,807 cases; the unified international standard unit pg/ml was adopted, with a conversion factor of 3.67), and heterogeneity was observed among various trials ( P <0.00001, I 2  = 96%). Therefore, a random-effect model was used for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Current consensus is that a higher dose leads to the retrieval of more oocytes but similar pregnancy rates in standard patients (younger than 40 years of age, having two ovaries, a normal menstrual cycle and a normal basal FSH level) (Fauser et al, 2008;Hayden, 2008). Firouzabadi et al, (2010) recommended dose of rFSH was 100 to 250 IU/day in the agonist protocol and 150 or 200 IU/day in the GnRH antagonist cycles. Kolibianakis et al, (2006) propose that the stimulation duration was shorter and there was less usage of rFSH used GnRH antagonist protocol as an advantage when compared with agonist treatment, and Huang et al, (2011) showed some advantages of the GnRH antagonist protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, GnRH-ant reduces the dosage and length of the exogenous gonadotropin treatment. Comparative studies between the two analogues have suggested that the use of antagonists is associated with a shorter duration of the ovulatory stimulus and a decreased incidence of ovarian hyperstimulation syndrome (OHSS); however, the rates of pregnancy and live birth do not appear to be significantly affected, depending on the type of GnRH analogue used (Fauser et al, 2008;Hayden, 2008;Firouzabadi et al, 2010;Griesinger et al, 2010;Pu et al, 2011;Maldonado et al, 2013;Orvieto & Patrizio, 2013). Multiple follicular development is achieved by extending the period during which the concentration of FSH remains above the FSH threshold necessary to stimulate single-follicular growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Одни авторы в его основу закладывают количество неэффективных циклов ВРТ (2 и более; 3 и бо-лее) [3][4][5], другие -дополняют информацией о количестве и качестве перенесенных эмбри-онов [6]. Например, 8 эмбрионов на стадии дробления или 4 -на стадии бластоцисты в 2-6 циклах ЭКО [7]. По мнению профессора L. Polanski (2014), повторные неудачи ВРТ -это отсутствие имплантации, определяемой по уровню ХГЧ в сыворотке крови на 14-й день после переноса эмбрионов хорошего качества, в двух и более последовательных циклах ЭКО.…”
unclassified